La importancia de la obra de Ibn Ẓāfir para la historia de al-Andalus ["The importance of Ibn Ẓāfir’s work in the history of al-Andalus"] - FIERRO, Maribel (Al-Andalus Magreb, 2021)
Son notas y comentarios.